Quality of life: a multifaceted approach A review of “Measuring Equitable and Sustainable Well-being in Italy” by Enrico Giovannini and Tommaso Rondinella - Tania Georgia, Viciu; Balint, Antoniu Ovidiu; Costea, Carmen Eugenia (Journal of Economic Development, Environment and People, 2014)
The article constitutes a multifarious approach to describing the main directions provided by international bodies and scholar for measuring individual and national well-being. Constructing their analysis from a statistical point of view the authors describe and examine the quality of life framework built since the ‘40s. The focus point of the study is represented by the measures undertaken by Italian National Institute of Statistics (Istat) in order to provide a fair and harmonized measure of quality of life. Giovannini and Rondinella’s work stands out due to the fact that it provides a very well documented exploration for the well-being measurements.